1985
DOI: 10.1242/jeb.115.1.149
|View full text |Cite
|
Sign up to set email alerts
|

Fuels and pathways as designed systems for support of muscle work

Abstract: Muscle in all animals relies upon four potential sources of energy: ATP hydrolysis, phosphagen hydrolysis, fermentations or oxidative metabolism. Although the relative contributions of different fuels varies greatly in different organisms, in none is there a simple reliance on stored ATP. Muscle work therefore requires a balance between rates of utilization and formation of ATP, a provision supplied by one of the three remaining fuels and metabolic pathways. Useful endogenous fuels must be storable at high lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(4 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…It has been suggested that the OpDHs pathway serves as a major pathway of anaerobic metabolism for energy demand in the early stages of hypoxia stress in marine invertebrates, confirmed by the level of octopine increased gradually after anaerobic stress [13,17,35,44,56]. Some gastropod mollusks, such as C. toreuma, also relied on the OpDHs pathway for anaerobic metabolism under heat stress.…”
Section: Glucose-opine Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that the OpDHs pathway serves as a major pathway of anaerobic metabolism for energy demand in the early stages of hypoxia stress in marine invertebrates, confirmed by the level of octopine increased gradually after anaerobic stress [13,17,35,44,56]. Some gastropod mollusks, such as C. toreuma, also relied on the OpDHs pathway for anaerobic metabolism under heat stress.…”
Section: Glucose-opine Pathwaymentioning
confidence: 99%
“…Both LDH and OpDH pathways exhibited low efficiency yet high rates of energy production, thereby ensuring a constant flux of glycolysis and a steady supply of ATP by regulating the NADH/NAD+ ratio during hypoxia [23,34]. Increasing proline levels in M. edulis under short-term anaerobic stress could provide substrates for the glucose-opine pathway [13,17,35,36,44]. In addition, there was a study that proposed that the lactate pathway may have originated from opine pathways [13].…”
Section: Glucose-lactate Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…There appear to no reports on urate‐N excretion rates, and no reports on N‐waste excretion after exercise in this species. Exercise is of particular relevance to nitrogen metabolism because of the potential liberation of N‐wastes from increased rates of amino acid oxidation and adenylate breakdown (Hochachka, 1985). In the blue crab ( Callinectes sapidus ), ammonia‐N excretion increased greatly during enforced swimming activity in seawater (Booth et al, 1984; Milligan et al, 1989).…”
Section: Introductionmentioning
confidence: 99%